Absorption boost of TiO2 nanotubes by doping with N and sensitization with CdS quantum dots. Issue 17 (1st December 2017) - Bjelajac, Andjelika; Djokić, Veljko; Petrović, Rada; Bundaleski, Nenad; Socol, Gabriel; Mihailescu, Ion N.; Rakočević, Zlatko; Janaćković, Djordje
Abstract: A process of obtaining N-doped TiO2 nanotubes sensitized by CdS nanoparticles is presented, including detailed characterizations performed along the synthesis. Transparent TiO2 films consisting of nanotubes, 2.5 µm long and of 60 nm inner diameter, were obtained after anodization of a titanium film deposited onto FTO glass substrate. N-doping was achieved by annealing of TiO2 film in ammonia. X-ray Photoelectron Spectroscopy measurements showed that nitrogen was substitutionally incorporated in the TiO2 matrix, with the N:Ti concentration ratio of 1:100. The doping changed the optical properties of the material in such a way that the absorption edge was shifted from 380 nm to 507 nm, as observed from diffuse reflectance spectra. The influence of the microwave (MW) irradiation on the synthesized CdS quantum dots and their optical properties was investigated. It was shown that the diameter of CdS nanoparticles was increased due to releasing of S 2- ions from dimethyl sulfoxide (DMSO) as a consequence of the MW treatment. The (N)TiO2 films were then used as substrates for matrix assisted pulsed laser deposition of the CdS quantum dots with DMSO as a matrix. The laser parameters for the deposition were optimized in order to preserve the nanotubular structure open, the latter being an important feature of this type of photoanode. The structure obtained under optimized conditions has an additional absorption edge shift, reaching 603 nm.